User satisfaction towards lift service at low cost housing in Klang Valley / Mohd Zarul Ashraf Mohamad Nor - Mohamad Nor, Mohd Zarul Ashraf (2014)
Nowadays, the increase of population in the developed areas of the Klang Valley is increasing. The rapid migration of population from rural areas towards urban areas to turn their lives has created a low cost housing in the vicinity of the Klang Valley. Low-cost housing typically has a height of between five to twenty levels of floors. Lift is the main transport system in a high rise building. Lack of maintenance will cause problems to the operating of lift service system and also will give an effect on the quality of life of resident sat low-cost housing. Most of the government buildings are not regularly maintained because most of the faults cannot be distinguished at the early stage and it is very common to see as stated by former Prime Minister of Malaysia, Tun Abdullah Ahmad Badawi and also the management of transportation system practiced in Malaysia is still primitive and not systematic in lift service system. According to Jabatan Kesihatan dan Keselamatan Pekerjaan (JKKP), the incidents of lift user always occur in low cost apartment. A poor quality of lifts service system is related to describe about the living inlow cost apartment. The aim is to improve of lift service system towards lift user at low cost housing in Klang Valley and supported by three objectives such as study the lift maintenance management system identified the level of satisfaction among lift user and give recommendations in improving lift service. For the research methodology, it is using primary sources, secondary sources such as previous journal and references books,interview session and questionnaire survey. To achieve the aim and objectives, three ofthe case study was selected to study about the user satisfaction towards lift service inKlang Valley. The first case study is PPR Desa Mentari at Bandar Sunway, Petaling Jaya, PPR Kg Baru Hicom at Seksyen 26, Shah Alam and lastly apartment Cempaka, Bandar Baru Klang at Bukit Raja. 100 questionnaires were distributed to 2 case studies at PPR Kg Baru Hicom and PPR Desa Mentari and 60 questionnaires were distributed at apartment Cempaka. During the survey, the findings shows that majority of the respondents at PPRKg Baru Hicom and PPR Desa Mentary are not satisfied with lift service at their residential while majority of the respondents at apartment Cempaka are very satisfied with lift service at their residential.